The MIC3 Gene of Toxoplasma gondii Is a Novel Potent Vaccine Candidate against Toxoplasmosis - Ismael, Alaa Bassuny (American Society for Microbiology, 2003)
Infection with the intracellular protozoan parasite Toxoplasma gondii causes serious public health problems and is of great economic importance worldwide. The micronemal protein MIC3, which is a potent adhesin of T. gondii, could be a significant candidate vaccine against toxoplasmosis. In this study, all CBA/J mice intramuscularly vaccinated with a plasmid encoding the immature form of the MIC3 protein (pMIC3i) produced specific anti-MIC3 immunoglobulin G (IgG) antibodies, and their sera displayed high antibody titers. This response was increased by the coadministration of a plasmid encoding the granulocyte-macrophage colony-stimulating factor (pGM-CSF). Similarly, a specific and significant cellular immune response was obtained in mice immunized with pMIC3i, and this response was markedly enhanced by pGM-CSF coadministration. The cellular immune response was associated with the production of gamma interferon IFN-γ and interleukin-2 (IL-2), indicating that this was a Th1-type response. This was confirmed by the production of large amounts of IgG2a. Mice immunized with pMIC3i displayed significant protection against an oral challenge with T. gondii 76K cysts, exhibiting fewer brain cysts than did the control mice. Coadministration of pGM-CSF enhanced this protection. In conclusion, this study describes the design of a potent DNA vaccine encoding the novel T. gondii target antigen, MIC3 protein, that elicits a strong specific immune response as well as providing effective protection against T. gondii infection. In the attempt to achieve complete protection against toxoplasmosis, MIC3 is a good candidate vaccine which could be combined with other relevant and previously described candidates, such as SAG1 and GRA4.